A Study of the Distribution of Some Noble Metals in the Merensky Horizon, Bushveld Igneous Complex - Teruta, Yuko (My University, 1974)
Neutron activation analysis has been applied to the simultaneous determination of Pt, Pd, Ir and Au in a diamond drill core from the Lonrho property (Western Platinum Limited) on the Merensky horizon, Bushveld Igneous Complex, South Africa.
Analytical results for Pt, Pd, Ir and Au in a total of 65 samples, including 25 whole rock, 19 separated sulphide and 21 oxide samples are presented. Chemical analyses by fusion-gravimetric and atomic absorption methods are used to determine S, Cr, Ni and Cu in whole rock samples. Profiles along the core length were obtained for the four noble metals and these were correlated with the mineralogical and petrographic character of the core. The sulphide and oxide data were used to evaluate the proportion of total platinum group metals contributed by these mineral phases.
Keywords: Geology; Geology